(untitled) (The Pakistan Development Review, 2003)
Audio-visual services play a crucial and formative role in any society. These services are closely linked to the preservation of cultural identity and social values, and play a major role in shaping public opinion, safeguarding democratic system and developing creative potential. Due to these reasons, governments of both developed and developing countries not only provide direct and indirect incentives to their domestic industries but also strictly regulate the content of audio-visual media. During the Uruguay Round of WTO (World Trade Organisation) negotiations, audio-visual service sector witnessed limited liberalisation. Even major players such as the EU, Australia and Canada did not make any commitments to liberalise trade in these services. This was primarily to protect the domestic industries from foreign competition, promote their growth and to protect the cultural heritage of the nations from foreign influence. Many countries have repeatedly raised concerns about the capability of the GATS (General Agreement on Trade in Services) framework to take into account the democratic, cultural and social aspects. Others have explained that audio-visual sector is largely covered by domestic regulations and normal trade rules are not applicable to these services.